Influence of retronectin-mediated T-cell activation on expansion and phenotype of CD19-specific chimeric antigen receptor T cells - Stock, Sophia; Hoffmann, Jean-Marc; Schubert, Maria-Luisa; Wang, Lei; Wang, Sanmei; Gong, Wenjie; Neuber, Brigitte; Gern, Ulrike; Schmitt, Anita; Müller-Tidow, Carsten; Dreger, Peter; Schmitt, Michael; et al. (Human gene therapy, 2018)
Enhanced in vivo expansion, long-term persistence of chimeric antigen receptor T (CART) cells, and efficient tumor eradication through these cells are linked to the proportion of less-differentiated cells in the CART cell product. Retronectin is well established as an adjuvant for improved retroviral transduction, while its property to enrich less-differentiated T cells is less known. In order to increase these subsets, this study investigated the effects of retronectin-mediated T-cell activation for CD19-specific CART cell production. Peripheral blood mononuclear cells of healthy donors and untreated chronic lymphocytic leukemia (CLL) patients without or with positive selection for CD3+ T cells were transduced with a CD19.CAR.CD28.CD137zeta third-generation retroviral vector. Activation of peripheral blood mononuclear cells was performed by CD3/CD28, CD3/CD28/retronectin, or CD3/retronectin. Interleukin-7 and -15 were supplemented to all cultures. Retronectin was used in all three activation protocols for retroviral transduction. Expansion was assessed by trypan blue staining. Viability, transduction efficiency, immune phenotype, and cytokine production were longitudinally analyzed by flow cytometry. Cytotoxic capacity of generated CART cells was evaluated using a classical chromium-51 release assay. Retronectin-mediated activation resulted in an enrichment of CD8+ cytotoxic CART cells and less-differentiated naïve-like T cells (CD45RA+CCR7+). Retronectin-activated CART cells showed increased cytotoxic activity. However, activation with retronectin decreased viability, expansion, transduction efficiency, and cytokine production, particularly of CLL patient-derived CART cells. Both retronectin-mediated activation protocols promoted a less-differentiated CART cell phenotype without comprising cytotoxic properties of healthy donor-derived CART cells. However, up-front retronectin resulted in reduced viability and expansion in CLL patients. This effect is probably attributed to the retronectin-mediated activation of B cells with prolonged CLL persistence. Consequently, CART cell expansion and generation failed. In summary, activation with retronectin should be performed with caution and may be limited to patients without a higher percentage of tumor cells in the peripheral blood.
Gesehen am 17.04.2020